How do complex phenotypes evolve? Solving the “gene for X” problem with atavisms, homeosis, and other evo-devo surprises - Werth, Alexander J (Open Science Journal, 2021)
Helping students learn how major phenotypic shifts evolve is a major hurdle for biology educators. Fortuitously, teachers can exploit the oft-misunderstood “gene for X” concept to explain how evolution, and complex phenotypes, often turn on single changes to regulatory genes governing expression of structural genes during development. This explains how one gene can make a big difference, and relates microevolution relates to macroevolution, a frequent hang-up for evolution deniers. Although complex traits such as intelligence do not derive from a single gene, minor tweaks in gene regulators produce atavisms (sudden appearance of “throwback” features), homeotic mutants (whose altered features stem from shifts in developmental timing and location), and other major changes in organismal morphology. Biology educators must explain how evo-devo mechanisms profoundly shift the course of evolution and drive phenotypic change. An adult form does not evolve into another, but underlying development readily evolves.